Phytocystatin CsinCPI-2 prevents bone loss in ligature-induced periodontitis by inhibition of inflammation and osteoclastogenesis - Da Ponte Leguizamón, Natalia (2021)
Periodontal disease (PD) is a polymicrobial chronic inflammatory condition of the supporting tissues around the teeth, leading to the destruction of surrounding connective tissue. During the progression of PD, osteoclasts play a crucial role in the resorption of alveolar bone that eventually leads to the loss of teeth if the PD is left untreated. Therefore, the development of anti-resorptive therapies targeting bone-resorbing cells will significantly benefit the treatment of PD. Here, we demonstrate the inhibitory effect of CsinCPI-2, a novel cysteine peptidase inhibitor from the orange tree, on periodontitis-induced inflammation, alveolar bone loss and osteoclast differentiation. Using the ligature-induced periodontitis model in mice, we demonstrate that treatment with CsinCPI-2 (0.8 µg/g of body weight) significantly reduced inflammatory cell infiltrate in the connective tissue and preventes the loss of alveolar bone mass (BV/TV) caused by PD, effects associated with diminished numbers of TRAP-positive multinucleated cells. Furthermore, CsinCPI-2 significantly down-regulated the numbers of inflammatory cells expressing CD3, CD45 MAC387 and IL-1β. In vitro, CsinCPI-2 inhibited RANKL-induced TRAP+ multinucleated osteoclast formation in mouse bone marrow macrophage (BMM) cultures in a concentration-dependent manner. This effect was not due to cytotoxicity, as demonstrated by the MTT assay. CsinCPI-2 inhibited RANKL-induced mRNA expression of Acp5, Calcr and Ctsk, as well as the RANKL-induced up-regulation of Nfatc1, a crucial transcription factor for osteoclast differentiation. Our findings demonstrate that CsinCPI-2 prevents bone loss induced by PD by controlling the inflammatory process and acting directly on osteoclastogenesis, suggesting an interesting potential for CsinCPI-2 in the strategy for PD treatment.